Development process and patient usability preferences for a touch screen tablet–based questionnaire. (March 2020) - Lam Shin Cheung, Victor; Kastner, Monika; Sale, Joanna EM; Straus, Sharon; Kaplan, Alan; Boulet, Louis-Philippe; Gupta, Samir
We sought to design a touch tablet asthma questionnaire while identifying patient preferences for usability features of such questionnaires. We created an evidence-based prototype and employed rapid-cycle design (semi-structured focus group testing, analysis, corresponding modifications, re-testing) with asthma patients aged ⩾16 years. We analyzed transcripts using deductive and inductive content analysis. Quantitative measures included Likert-type-scale responses, the System Usability Scale, and questionnaire completion times. There were 20 participants across five focus groups (15/20 female, age 49.1 ± 15.6 years). Usability-related themes included (1) "Touch Technology" (hygiene, touch technology familiarity, ease of use) and (2) "Questionnaire Design" (visual characteristics, navigation). Completion time was 11.7 ± 5.9 min. Summative Likert-type scale responses suggested high system usability, as did a System Usability Scale score of 84.2 ± 14.7. In summary, Attention to specific technology- and design-related preferences can result in a highly usable patient-facing touch tablet questionnaire. Our findings can inform touch questionnaire design across other diseases.